Abstraction reflective student in problem solving of Mathematics based cognitive style - Anies Fuady; Purwanto; Susiswo; Swasono Rahardjo (Center for Humanities and Innovation Studies, 2019)
The student's reflective abstraction ability in solving problems is necessary because the result of a person's reflective abstraction is a scheme used to understand something, finding solutions or solving problems. Besides, reflective abstractions are essential to higher mathematical, logical thinking as they occur in logical thinking in children. Therefore, to develop a reflective abstraction notion of high-level mathematical thinking, it is necessary to separate what is an essential feature of reflective abstraction, reflect its rules on higher mathematics, recognize and reconstruct it so that a similar theory of knowledge Mathematics and its instructions. While research that will researchers do is to know how the process of reflective abstraction of students in solving problems in terms of cognitive style. This is because the cognitive style is closely related to how to receive and process all information, especially in learning. The various trends in their learning can be identified and then classified whether the child belongs to an independent field cognitive style (thinking tends to have the independence of views) or field dependent.